Analisis Fenomena Kehilangan Air Sungai Cisuwarna - Syariman, Petrus; Hendarmawan, Hendarmawan (JURNAL TEKNIK HIDRAULIK, 2010)
Discharge from Cisuwarna River is one of the main inflows to Rawa Danau highly expected by local people either upstream or downstream.  Part of water loss of Cisuwarna caused not optimum domestic water use.   Water loss indication can be seen from the simulation results by using SSARR model that calculated discharge greater than observed.    The methods used for water loss analysis are simultaneous discharge measurement, rainfall – runoff  and coefficient correlation analysis, and geological map interpretation.  The analysis result has proven that the average water loss at Cisuwarna is about 12 .4 million cumec per year or about 45% of calculated discharge.  Water loss is assumed to flow into the fault before flowing into Rawa Danau.  Water deficit is always going through every year in Rawa Danau.Keywords:   Water loss, calculated discharge, rainfallrunoff, faults, water deficit.